A Culturally Responsive Intervention for Addressing Problematic Behaviors in Counseling Students. (25th February 2013) - Goodrich, Kristopher M.; Shin, Richard Q.
<x xml:space="preserve">Abstract</x> Counseling faculty serve as gatekeepers to protect the public from trainees who demonstrate significant deficiencies in professional functioning. Two issues that have not been thoroughly examined are how different cultural values may intersect with the assessment of appropriate professional competencies and whether the multicultural environment of programs is considered when assessing potentially problematic students. The authors suggest a group systems intervention and provide implications and recommendations for counselor educators.